HEMOSTATIC SYSTEM DISORDERS IN PATIENTS WITH COXARTHROSIS OF III–IV STAGES AFTER TOTAL HIP ARTHROPLASTY (LITERATURE REVIEW) - Vysotskyi, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2025)
Objective. Тo analyze the current state of diagnosis and prevention of hemostatic disorders in patients with Kellgren-Lawrence grade III-IV coxarthrosis after total hip arthroplasty based on s cientific l iterature. M ethods. A search was performed in PubMed, Web of Science, Google Scholar and Scopus. Using MeSH and keywords such as: "inflammatory markers", "coxarthrosis", "thromboembolism", "tranexamic acid", "anticoagulants", "inflammation", "fibrinolysis", "D-dimer", "arthroplasty", "hypercoagulability", "plasminogen". Results. An important issue in the prevention of thromboembolic complications during total hip arthroplasty is to determine the dynamics of fibrinolysis disorders. Thus, it was found that hip arthroplasty is characterized by an increase in inflammatory markers in the blood and hemostatic disorders. Conclusions. In clinical orthopedics, after hip arthroplasty in patients with coxarthrosis of III-IV stages, complications often occur in the form of hemostatic disorders, which are accompanied by the development of deep vein thrombosis of the extremities, in severe cases — pulmonary embolism. These complications are monitored based on the results of determining the markers of the hemostatic system, which are examined before and after surgery. It has been proven that there are many different factors that affect the development of hemostatic disorders in the body. The age factor, as elderly patients have their own metabolic characteristics and altered rheological properties of blood. Increased body weight, in particular, obesity, is also an important factor that cannot be ignored in clinical practice. To date, clear clinical and laboratory criteria for assessing the hemostatic system and a list of biochemical markers of connective tissue to monitor the condition of patients before and after joint replacement in the context of modern anticoagulant regimens remain to be defined.